Kohesi dan Koherensi sebagai Dasar Pembentukan Wacana yang Utuh - I Nyoman Mandia (Politeknik Negeri Bali, 2017)
An understanding of cohesion and coherence greatly helps one writer in writing a good and correct discourse. In theory, cohesion and coherence are different, but after practicing these terms it is quite difficult to distinguish. Therefore, it is very important to do real action, namely learning to master the language, especially writing, through regular training and continuous. So there are two things that are necessary to achieve the writing skill of writing knowledge and practicing writing because writing is an integrated language skill aimed at producing something called writing. In the discourse, in addition to the presence of marker cohesion, also tucked in support of keherensi. A discourse does not have to be explicitly loading a grammatical tool (conjunction) that can connect one idea in other words, the logical relationship between the parts in the discourse can be created without the grammatical tool.